2006
DOI: 10.1073/pnas.0604933103
|View full text |Cite
|
Sign up to set email alerts
|

Modern Quaternary plant lineages promote diversity through facilitation of ancient Tertiary lineages

Abstract: One of the most important floristic sorting periods to affect modern plant communities occurred during the shift from the wet Tertiary period to the unusually dry Quaternary, when most global deserts developed. During this time, a wave of new plant species emerged, presumably in response to the new climate. Interestingly, most Tertiary species that have been tracked through the fossil record did not disappear but remained relatively abundant despite the development of a much more unfavorable climate for specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
253
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 254 publications
(266 citation statements)
references
References 36 publications
7
253
1
5
Order By: Relevance
“…Our assumption is in agreement with Valiente-Banuet et al (2006) who reported that a large number of Tertiary relict species in Mediterranean climate ecosystems appear to have been preserved by the facilitative effects of other species. Nevertheless, whether A. sempervirens is a modern Quaternary plant lineage is not clear.…”
Section: Probability Of Occurrence and Biotic Interactionssupporting
confidence: 82%
“…Our assumption is in agreement with Valiente-Banuet et al (2006) who reported that a large number of Tertiary relict species in Mediterranean climate ecosystems appear to have been preserved by the facilitative effects of other species. Nevertheless, whether A. sempervirens is a modern Quaternary plant lineage is not clear.…”
Section: Probability Of Occurrence and Biotic Interactionssupporting
confidence: 82%
“…In addition, some clades may have been more diverse in the past but were subsequently replaced by members of sister clades that diversified in later periods of the Cenozoic. The replacement of species by close relatives from the same genera or family where similar ecologies already exist is thought to be a significant contribution to the persistence and stability of plant communities over significant time periods (DiMichele & Philips 1996;Valiente et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we found that Trientalis occurrence is highly related to overstorey cover rather than topographic microclimate, suggesting that small shifts in climate may have little effect on distribution if overstorey cover does not significantly change, whereas loss of overstorey due to increasingly severe or frequent fires could have much more drastic consequences. Facilitative effects of canopy cover may also explain patterns such as persistence of species with 'cool-adapted' traits through long-term drying trends (Valiente-Banuet et al, 2006) and the positive effect of forest density on tree regeneration niche (Dobrowski et al, 2015). These results also imply that changes in biotic conditions independent of climate could lead to shifts in distribution and abundance that were not predicted by climate-based models.…”
Section: Discussionmentioning
confidence: 51%